Rekonstruksi Kewenangan Pengawasan Indikasi Geografis Produk Lokal - Moh. Fahrial Amrulla (Postgraduate University of Merdeka Malang, 2026)
This article examines the ambiguity of supervisory authority over Geographical Indications under Article 71 paragraph (1) of Law Number 20 of 2016 concerning Marks and Geographical Indications. The phrase “in accordance with their authority” creates normative uncertainty because it does not clearly define the scope, mechanism, institutional responsibility, and legal consequences of supervision conducted by central and regional governments. This study aims to analyze the construction of normative ambiguity in Article 71 paragraph (1) and formulate a reconstruction model for regulating supervisory authority over Geographical Indications in order to achieve legal certainty. This research applies a normative legal method using statutory and conceptual approaches. The legal materials are analyzed through grammatical, systematic, and teleological interpretation. The findings show that the existing regulation has not provided an operational division of supervisory authority between central and regional governments. The ambiguity affects legal certainty in maintaining the reputation, quality, characteristics, use, and utilization of Geographical Indications. Therefore, normative reconstruction is required by affirming the authority of central government as standard-setter, national coordinator, evaluator, and administrative decision-maker, while regional governments should be clearly authorized as direct supervisors of Geographical Indication products within their territories